Programming for Computations - Python A Gentle Introduction to Numerical Simulations with Python 3.6 - Linge, Svein (Texts in Computational Science and Engineering, 2020)
Mathematics; Computer mathematics; Numerical analysis; Computer software; Numerical analysis